Biodiversity of marine fishes from shellmounds of ilha grande bay, Rio de Janeiro, Brazil - Barros Mendes, Augusto; Pereira Silva, Edson; Corrêa Luz Souza, Rosa Cristina (Revista Chilena de Antropología, 2015)
Ilha Grande Bay region comprises a large biological biodiversity distributed in different ecological compartments and also is surrounded by shellmounds dating between 8.000 and 2.000 years B.P. A check list of Fish fauna from 11 of these shellmounds was done and compared with nowadays fish inventory for the region. Most of the species recorded for the shellmounds belongs to the class Chondrichthyes (53.5%), which is represented in the check list by 9 families and 38 species, being Carcharhinus Blainville, 1816, the genus with the highest number of species. Regarding the Osteichthyes, 16 families and 33 species were recorded. Micropogonias furnieri (Desmarest, 1823) was recorded for all sites. Most of the fish identified has a wide distribution in the western Atlantic (35.2%), pelagic behavior (35.2%) and inhabits estuarine environments (36.6%). Almost all the records are composed of noble fish representing top chain carnivorous which can reach large sizes, especially the Chondrichthyes. Comparisons done with current ichthyofauna data for the area (Ministry of Environment Brazil) have shown high similarity between past and present pattern of biodiversity, although some discrepancies were found for comparisons sorting species by their ecological compartments. The results show that shellmounds are valuable repositories of information concerning species composition in the past and, therefore, to the study of evolution of biodiversity patterns over time. Data on this nature are important for conservation and management strategies.